Extent of cardiovascular medications dispensing practice without a prescription: Self-reported and simulated patient-based study at community pharmacies in Northwest Ethiopia - Ashenafi Kibret Sendekie; Asrat Elias Ergena; Eyayaw Ashete Belachew; Asmamaw Emagn Kasahun; Masho Tigabie Teklie; Adeladlew Kassie Netere (Taylor & Francis Group, 2023)
Abstract Background Critical actions are required for the proper administration of medications to patients with cardiovascular diseases. However, there has been an increase in irrational use of cardiovascular drugs. The purpose of this study was to determine the extent of non-prescription cardiovascular medicine dispensing practices at community drug retail outlets (CDROs) in Gondar, Northwest Ethiopia. Methods A cross-sectional survey and simulated patient-based visits were employed at the CDROs in Gondar City, Northwest Ethiopia between June 1 and July 20, 2022. The cross-sectional component that assessed the self-reported practices used a standardized self-reported questionnaire. A simulated patient (SP) case scenario, using different tracer prescriptions only for cardiovascular medications, allowed for the observation of real-world dispensing procedures. SPSS version 22 was used for the data entry and analysis. Results The cross-sectional study approached 76 CDROs, and 71 of them agreed to take part (93.4% response rate). More than half of the respondents (53.5%) were males, with a mean (SD) age of 33.5 ± 9.1 years. Overall, the current self-reported survey showed that 59.2% of the participants provided cardiovascular drugs without a prescription. A total of 213 simulated visits were conducted. Considering all SP scenarios, the percentage of cardiovascular drugs dispensed without a prescription increased to 88.7%. Besides, more than 90% of pharmacists did not demand the SP to have a prescription, did not advise them to visit doctors or clinics, and did not inquire as to whom the medication was required. Conclusion A significant proportion of CDROs dispensed cardiovascular medications without a prescription. The findings highlight the disparity between self-reported and actual CDRO practices. Additionally, nearly all of the CDROs approached made it simple to obtain cardiovascular medications. Stakeholders could adherently follow the CDROs' practices to improve their proper dispensing procedures.